Transactions on Computational Collective Intelligence XV - Nguyen, Ngoc Thanh; Kowalczyk, Ryszard; Corchado, Juan Manuel; Bajo, Javier; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
These transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the Semantic Web, social networks, and multi-agent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies, such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This 15special issue is dedicated to the International Conference on Practical Applications on Agents and Multi-Agent Systems (PAAMS 2012 and PAAMS 2013) held in Salamanca, Spain.
Building optimal macroscopic representation of complex multi-agent systems -- Understanding in the role of emotions in group dynamics in emergency situations -- Representation of the agent environment for traffic behavioral simulation -- Using LCS to exploit order book data in artificial markets.
Keywords: Artificial intelligence; Computational intelligence; Computer simulation; Computers; Artificial Intelligence; Computational Intelligence; Simulation and Modeling; Information Systems and Communication Service